Seasonal variations of triterpene acid contents in Viscum album L. on typical host trees of Hyrcanian forests - Soursouri, Arina; Hosseini, Seyed Mohsen; Fattahi, Farnoosh (Scientific reports, 2023)
Viscum album L. (mistletoe) is a semiparasitic plant of the Santalaceae family. A valuable group of bioactive compounds in mistletoe are triterpene acids (TTAs), which possess anti-inflammatory and anticancer properties. Parrotia persica and Carpinus betulus are the most common hosts of mistletoe in the Hyrcanian forests of Iran. This study was performed to compare the content of oleanolic acid (OA), betulinic acid (BA), and ursolic acid (UA) in the mistletoe foliage (stems and leaves) from P. persica and C. betulus in various seasons for the first time. The results showed that OA was the prevailing TTA in all samples, while UA was found in none of them. The maximum amount of OA (12.38 mg/g dry weight [DW]) and BA (1.68 mg/g DW) was detected in V. album from P. persica in summer. The minimum amount of OA (5.58 mg/g DW) and BA (0.72 mg/g DW) was observed in that growing on C. betulus in winter. However, the mistletoe from C. betulus showed the greatest level of OA in spring (9.06 mg/g DW) and BA in summer and autumn (0.92 and 0.97 mg/g DW, respectively). The data collected in this study complement existing research on this subject from around the world.